How trust can drive forward the user acceptance to the technology? In-vehicle technology for autonomous vehicle. (December 2018) - Adnan, Nadia; Md Nordin, Shahrina; bin Bahruddin, Mohamad Ariff; Ali, Murad
Graphical abstract: Highlights: Outline on the potential obstacles to consumer acceptance of autonomous vehicles. Establish theoretical framework following existing technology acceptance theory to explain the user acceptance process. Extend the current framework by adding ethical/legal implication into the discussion. Point out the limitations of current studies to be improved, and later propose improvements to the research topic. Abstract: The autonomous vehicle innovation has a potential effect on traffic and it's a widespread issue in the academic municipal. Based on its feature, autonomous vehicle is expected to improve traffic flow, reduce accidents, reduce social exclusion and improve the utility of time on travel. It is increasingly accepted that the next step to the evolution of human transportation is the replacement of human as the driver by the Artificial-intelligence-capable machine. Regardless, the challenges remain especially in convincing the consumers to switch to autonomous cars despite the apparent benefits. In the past, papers highlighted individual trust toward machine as the key point to encourage acceptance of autonomous cars. This paper seeks to highlight the ethical implications of the autonomous technology and how it is related to the user acceptance of the technology. This paper reviewed recent studies on the ethical implications of the autonomous vehicle and the user acceptance of the technology. A systematic review of papers from the literature was done using Scopus, ISI and Web of Science. The results of the review have shown that the level of trust, which may vary on the sociodemographic profile of the users, has been studied as one of the factors for user acceptance. Many researchers also highlight ethical implication as an important aspect of autonomous technology that needs to be tended to. The researcher proposes that ethical implication can be an important element of user trust toward autonomous technology. Hence, there is a need to embed ethical implication as a construct for user trust leading to user acceptance model in future studies. In the line of this research review researcher was addressed the following comprehensive groups: examination of autonomous vehicle topographies and flexibility prototypes, consequences for street traffic and connectivity to substructure (specifically in the urban areas with the medium and low density), communal attitudes and apprehensions, transportable behaviour and plea, possible business models, and strategy implications. Lastly, the main objective of this research article is to recognise critical problems for the growth of an effort cluster investigation to comprehend attitudes of possible manipulators of AVs and to highpoint autonomous vehicle growth issues for Malaysian lawful agencies.